Particles and fields in radio galaxies: a summary - Blandford, R (2002)
A summary is presented of a meeting on Particles and Fields in Radio Galaxies held in Oxford in August 2000. Recent detailed studies of radio maps and the first X-ray images from the Chandra X-ray Observatory, together with new capabilities in simulating hydromagnetic flows, are transforming our understanding of how jets are formed by accretion disks orbiting massive black holes, how these jets dissipate and how they inflate the giant radio-emitting lobes by which they were first identified. As they can be imaged in such detail, extragalactic radio sources remain central to the study of jet outflows in general although there is a strong convergence with corresponding studies of Galactic superluminal sources, gamma ray bursts and young stellar objects..